Assessing the Impact of Self-Medication with Antibiotics Among Medical Students : Assessing the Impact of Self-Medication with Antibiotics - Rehman, Sadia; Sarfraz, Muhammad Raza; Bano, Saira; Ismail, Aasia; Naveed, Asma; Malik, Anum (Pakistan Journal of Health Sciences, 2024)
Self-medication is different from self-care in that it uses drugs, which might be helpful or detrimental. According to a number of studies, improper self-medication carries significant health concerns like unpleasant side effects, prolonged pain, and drug dependence. Objective: To explore the adverse effects of self-medication with antibiotics among medical students. Methods: Over the course of seven months, from November 2022 to May 2023, a multi-institutional cross-sectional study was conducted at the University Medical and Dental College of the University of Faisalabad and Bahria University Health Sciences, Karachi (BUHS). The ethical approval was obtained from the Ethical Review Committee of BUHS (Ref: ERC/05/2023) and Institutional Review Board of The University of Faisalabad (Ref: TUF/IRB/153/2022). A sample size was calculated by OpenEpi website calculator. Microsoft excel was used to store the data and IBM SPSS version 23.0 was used for data analysis. A self-designed performa was used to collect data. Results: There was a total of 1340 students in our survey, and an equal number of students 670 (50%) were recruited from each institute. 414 (61.8%) students from BUHS and 494 (73.7%) from UMDC were found to have self-medication practices. 39.9% and 38.2% of the students from 1st year and 2nd year of medical education were found to self-medicate. 69.5% of the hostelite students were found to self-medicate antibiotics. Conclusions: Our research can be concluded as self-medication of antibiotics is a common practice among future health care professionals, with the highest incidence seen in the 1st and 2nd year of medical education. Several adverse symptoms arising due to this practice were seen with the highest being tiredness and dizziness.